Kesan pengaruh kecerdasan emosi, personaliti dan estim kendiri ke atas komitmen terhadap organisasi - Johar, Siti Sarawati (2015)
Employees’ commitment contributes towards effectiveness in an organization. However, commitment can be impaired in the absence of the emphasis placed on psychological factors. These psychological factors that affect commitment are emotional intelligence, personality and self-esteem. Therefore, this study aims to investigate how these factors influence commitment. The research tested the impact of emotional intelligence on commitment; impact of emotional intelligence on self-esteem; impact of self-esteem on commitment; identified personality traits as moderators in the relationship between emotional intelligence and self-esteem; and determined the role of self-esteem as a mediator in the relationship between emotional intelligence and commitment. 162 civil servants employed by the Local Authority (LA) in the southern zone of peninsular Malaysia were chosen as respondents. Measurement tools used in the study are Emotional Intelligence Self-Description Inventory (EISDI), Eysenck Personality Questionnaire-Revised Short Form (EPQR-S), Rosenberg Self-Esteem Scale (RSES) and Employee Commitment Survey Revised Version (ECS-R). Descriptive and inferential analyses of the data included simple regression, multiple regression, and hierarchical regression. The results showed that the emotional intelligence dimension of facilitating thinking with emotion, and dimension of regulation and management of emotion had an impact on affective and normative commitment. In addition, the dimension of facilitating thinking with emotion had an impact on continuance commitment. Next, the dimension of regulation and management of emotion had an impact on self-esteem whereas the other three dimensions of emotional intelligence had no impact. However, self-esteem had an impact on affective and normative commitment. Personality traits such as extraversion, neuroticism and psychoticism do not have a function as moderators in the relationship between emotional intelligence and self-esteem. The most important finding from this study is that self-esteem served as a partial mediator in the relationship between dimension of regulation and management of emotion with affective and normative commitment. From the study, it is proposed that strength of emotional intelligence and self-esteem among employees should be the focus in order to improve employees’ commitment. This study can also be used as a reference for any organization to improve their employees’ commitment.